Delivery of Rice Gall Dwarf Virus Into Plant Phloem by Its Leafhopper Vectors Activates Callose Deposition to Enhance Viral Transmission - Yi, Ge; Wu, Wei; Wei, Taiyun (Frontiers in Microbiology, 2021)
Rice gall dwarf virus (RGDV) and its leafhopper vector Recilia dorsalis are plant phloem-inhabiting pests. Currently, how the delivery of plant viruses into plant phloem via piercing-sucking insects modulates callose deposition to promote viral transmission remains poorly understood. Here, we initially demonstrated that nonviruliferous R. dorsalis preferred feeding on RGDV-infected rice plants than viruliferous counterpart. Electrical penetration graph assay showed that viruliferous R. dorsalis encountered stronger physical barriers than nonviruliferous insects during feeding, finally prolonging salivary secretion and ingestion probing. Viruliferous R. dorsalis feeding induced more defense-associated callose deposition on sieve plates of rice phloem. Furthermore, RGDV infection significantly increased the cytosolic Ca2+ level in rice plants, triggering substantial callose deposition. Such a virus-mediated insect feeding behavior change potentially impedes insects from continuously ingesting phloem sap and promotes the secretion of more infectious virions from the salivary glands into rice phloem. This is the first study demonstrating that the delivery of a phloem-limited virus by piercing-sucking insects into the plant phloem activates the defense-associated callose deposition to enhance viral transmission.